Association between air pollution, altitudes, and overweight/obesity in China - Yugen Wang; Muchun Yu; Yanyan Liu (Frontiers in Public Health)
BackgroundAir pollution and altitudes are important obesogenic environmental risks. No studies have examined the influence of the co-exposure of these two risks and Body Mass Index (BMI). We discuss the concentration–response (C–R) relationships and potential mechanisms between nine air pollution, altitudes, and BMI.MethodsData from 38,617 individuals aged 18–90 years in the China Family Panel Survey were used. Nine air exposure variables–Particulate Matter 2.5 (PM2.5), Sulfur dioxide (SO2), Carbon monoxide (CO), Nitrogen dioxide (NO2), Ozone (O3), Black Carbon (BC), Methane (CH4), Ammonia (NH3), and Non–Methane Volatile Organic Compounds (NMVOCs)–and altitude grid data were generated through the combination of satellite remote sensing inversion data and nationally representative surveys. Bayesian kernel machine regression and the moderated chain–mediation model were employed to examine the C–R relationships and potential mechanisms.ResultsFour air pollution–PM2.5, BC, NMVOCs, and CH4-were positively associated with OW/OB. A “negative–positive–negative correlation” pattern across low altitudes (τ30 to τ55, 73.77–403.87 m), medium altitudes (τ55 to τ75, 403.88–944.73 m), and high altitudes (τ75 to τ99, 944.74–2,610.72 m) was revealed for the correlation between altitudes and BMI. Altitudes negatively moderated the relationship between air pollution and BMI. A chain mediator, consisting of physical activity and sleep quality sequentially, partially mediated the association between air pollution and BMI.ConclusionsCo-exposure of air pollution and altitude had a complex influence on individual BMI. Maintaining a healthy environment is important for the joint prevention and control of obesity.